Nutritional Counseling Promotes Changes in the Dietary Habits of Overweight and Obese Adolescents with Polycystic Ovary Syndrome - Carolo, Adriana Lúcia; Mendes, Maria Célia; Rosa e Silva, Ana Carolina Japur de Sá; Vieira, Carolina Sales; Silva de Sá, Marcos Felipe; Ferriani, Rui Alberto; Reis, Rosana Maria dos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective To evaluate the effects of nutritional counseling on the dietary habits and anthropometric parameters of overweight and obese adolescents with polycystic ovary syndrome (PCOS).Methods This was a prospective, longitudinal and auto-controlled study. Thirty adolescents aged 13–19 years-old, diagnosed with PCOS received nutritional counseling and were followed-up for 6 months. After the follow-up period, the results were evaluated through body weight, body mass index (BMI) and waist circumference (WC).Results Sixty-percent of the adolescents adhered to the nutritional counseling and, of these, 50% lost weight. Adolescents who lost weight changed their dietary habits by adopting hypocaloric diets and eating more meals per day, as per nutritional counseling. The waist circumference (WC) decreased significantly, although the body weight decreased non-significantly after adoption of a hypocaloric diet.Conclusion Although there was no significant weight loss, there was a considerable reduction in the WC associated with hypocaloric diets and with eating a greater number of meals per day.
Keywords: obesity; polycystic ovary syndrome; adolescents; weight loss; nutritional guidance